A meta-analysis of the effects of transcranial direct current stimulation combined with cognitive training on working memory in healthy older adults - Lv, Yanxin; Wu, Shuo; Nitsche, Michael A.; Yue, Tian; Zschorlich, Volker R.; Qi, Fengxue (Frontiers in Aging Neuroscience, 2024)
Background Working memory (WM) loss, which can lead to a loss of independence, and declines in the quality of life of older adults, is becoming an increasingly prominent issue affecting the ageing population. Transcranial direct current stimulation (tDCS), a non-invasive brain stimulation technique, is emerging as a potential alternative to pharmacological treatments that shows promise for enhancing WM capacity and May enhance the effects of cognitive training (CT) interventions. Objective The purpose of this meta-analysis was to explore how different tDCS protocols in combination with CT enhanced WM in healthy older adults. Methods Randomized controlled trials (RCTs) exploring the effects of tDCS combined with CT on WM in healthy older adults were retrieved from the Web of Science, PubMed, Embase, Scopus and the Cochrane Library databases. The search time period ranged from database inception to January 15, 2024. Methodological quality of the trials was assessed using the risk-of-bias criteria for RCTs from the Cochrane Collaboration Network, and RevMan 5.3 (Cochrane, London, United Kingdom) was used for the meta-analysis of the final literature outcomes. Results Six RCTs with a total of 323 participants were ultimately included. The results of the meta-analysis show that tDCS combined with CT statistically significantly improves WM performance compared to the control sham stimulation group in healthy older adults [standard mean difference (SMD) = 0.35, 95% CI: 0.11–0.59, I2 = 0%, Z = 2.86, p = 0.004]. The first subgroup analysis indicated that, when the stimulus intensity was 2 mA, a statistically significant improvement in WM performance in healthy older adults was achieved (SMD = 0.39, 95% CI: 0.08–0.70, I2 = 6%, Z = 2.46, p = 0.01). The second subgroup analysis showed that long-term intervention (≥ 10 sessions) with tDCS combined with CT statistically significantly improved WM compared to the control group in healthy older adults (SMD = 0.72, 95% CI: 0.22–1.21, I2 = 0%, Z = 2.85, p = 0.004). Conclusion tDCS combined with CT statistically significantly improves WM in healthy older adults. For the stimulus parameters, long-term interventions (≥ 10 sessions) with a stimulation intensity of 2 mA are the most effective.